On guerrilla warfare - Mao, Zedong 1893-1976 (University of Illinois Press, 2000)
One of the most influential documents of our time, Mao Tse-tung's pamphlet on guerrilla warfare has become the basic textbook for waging revolution in underdeveloped and emergent areas throughout the world. This book analyzes the nature and conduct of guerrilla warfare, and considers its implications for American policy.